Термохімічна поведінка саморозігріваючих систем на основі піролізного заліза в присутності багатоатомних спиртів - Кравченко, Олександр Володимирович; Пантелеймонов, Радислав Анатолійович; Першина, Катерина Дмитрівна (НТУ "ХПІ", 2017)
В роботі представлені експериментальні дані, основані на фізико-хімічних і термічних випробуваннях саморозігріваючих систем на основі піролізного заліза. Проведено дослідження впливу добавок гліцерину і пропіленгліколю на кінетику, ефективність нагріву і теплопередачі цих систем. На основі аналізу ефективності тепловіддачі і кінетики нагріву, обумовлених природою спирту і розведенням, встановлено вплив кількості ОН⁻ груп в молекулі спирту на формування областей локального розігріву. Показано, що однією із умов для локального розігріву в місці контакту розчина з порошком заліза є підвищення концентрації протонів. Отримані результати можна використовувати в термогальванічних елементах на основі заліза для стабілізації тангенціального градієнту температури.

Polyhydric alcohols, in particular glycerol, ethylene glycol and propylene glycol are widely used as the basis of liquids for convective heat transfer systems. In the last decades, systems based on polyhydric alcohols began to use to increase the coefficient of convective heat transfer in composite liquids containing dispersed solid-phase additives (SiO₂, Al₂O₃, CuO, metal powders, etc.). Iron and its oxides occupy a special place in additive series due to their ability to self-heating, magnetic and semiconductor properties, which forming conditions for non-adiabatic processes and initiate structural evolution of the iron compounds during heating. Also the nature of polyhydric alcohols and the concentration changes influence on the kinetic parameters of the exothermic reactions. In this situation the convective heat transfer is required condition of the efficiency work of self-heating systems based on pyrolysis iron. The following materials were used for making the samples: iron powder, expanded vermiculite with a thermal conductivity of 0.05 W/m·K, activated carbon, crystalline sodium chloride, carbamide, glycerin, propylene glycol. Samples temperatures were measured by contact thermometer WT-1, in the temperature range of -50 ... +300 °C (error of 0.01 °C). Experiment was carried out in air. Measurement was stopped at constant ambient temperature setting. The area of the contact with the heated surface was 2·10-4 m2. An analysis of the experimental results revealed the correlation between the values of the convective heat transfer coefficient (hc), thermal conductivity and heat capacity of the water-alcohol mixture by the dilution of alcohol solutions. The experimental data has shown that water is the initiator of an exothermic reaction. Glycerol unlike propylene glycol has no significant effect on the efficiency of the exothermic reaction. The change in the nature of the alcohol molecule, which is characterized by an increasing of number of hydroxyl groups, monotonically decreases with values of the pH of its aqueous solution. The relatively low pH values of propylene glycol solutions accelerate the corrosion of iron in presence of Fe²⁺ and Fe³⁺ ions. In this case heat transfer is increased by 1.5 times relative to the test system. Such behavior forms the conditions for local heating at the point of contact of the solution with iron powder. So propylene glycol additives can be used in iron-based thermal metal elements to stabilize the tangential temperature gradient. The obtained results can be used in iron-based thermogalvanic elements to stabilize the tangential temperature gradient and generation of the areas with supplementary concentration gradients.
Thermochemical behavior of self-heating systems based on pyrolysis iron in the presence of polyhydric alcohols
Keywords: саморозігрів; піроліз заліза; пропіленгліколь; термогальванічний елемент; self-heating; pyrolysis iron; glycerin; propylene glycol